Epidemiology and Pathogenesis of Bolivian Hemorrhagic Fever - Patterson, Michael (2014)
The etiologic agent of Bolivian hemorrhagic fever (BHF), Machupo virus (MACV) is reported to have a mortality rate of 25 to 35%. First identified in 1959, BHF was the cause of a localized outbreak in San Joaquin until rodent population controls were implemented in 1964. The rodent Calomys collosus was identified as the primary vector and reservoir for the virus. Multiple animal models were considered during the 1970’s with the most human-like disease identified in Rhesus macaques but minimal characterization of the pathogenesis has been published since. A reemergence of reported BHF cases has been reported in recent years, which necessitates the further study and development of a vaccine to prevent future outbreaks.